PERAN KOMUNIKASI ANTARA GURU, ORANGTUA, MASYARAKAT DALAM MENINGKATKAN KETERLIBATAN PEMBELAJARAN ANAK DI MADRASAH IBTIDAIYYAH - fina wasi'atul maghfiroh; Evi Khomariyah; Fuad Arif Noor (JRPD (Jurnal Riset Pendidikan Dasar), 2026)
This study examines the role of effective communication between teachers, parents, and the community in an effort to increase children's involvement in the learning process at MI Ma'hadul Ulum. This study is motivated by the importance of collaboration between three educational centers in creating a conducive learning environment for students' academic and social development. This study uses a qualitative approach with a case study method. Through a descriptive qualitative approach, this study analyzes the communication patterns that exist between the school, family, and the surrounding environment. The subjects of the study consisted of the principal, grade II teachers, grade IV teachers, two guardians, and one community leader. The results of the study indicate that there are forms of communication strategies in increasing student involvement in learning. The forms of formal communication include: a) holding regular meetings between teachers and parents, b) issuing circulars, c) using class WhatsApp group media. Forms of informal communication are as follows: a) conducting teacher visits to students' homes, b) holding unscheduled meetings between teachers and parents, c) involving the community in school activities. In addition to the above, it was found that the role of communication in increasing children's involvement in learning includes: a) synchronization of educational patterns at school and at home, b) more comprehensive monitoring of children's development, c) more effective resolution of learning problems, d) increasing children's motivation to learn.